PENERAPAN MODUL AJAR “SMARTLETTER” BERBASIS PROJECT BASED LEARNING UPAYA PENINGKATAN KETERAMPILAN MENULIS DAN SIKAP KOMUNIKASI SISWA MELALUI KARYA SURAT PRIBADI KELAS V SD NEGERI NGADIRGO 03 SEMARANG - Aysha Nadya Lintang Chantica; Panca Dewi Purwati (STKIP Subang, 2026)
This study aims to describe the implementation process and analyze the effectiviteness of the “SmartLetter” teaching module, based on Project Based Learning and Deep learning, in developing students’ writing and self-expression skills through personal letters in fifth-grade students at Ngadirgo 03 Elementary School, Semarang. This study used a mixed methods approach with a sequential explanatory design involving 30 students and one classroom teacher. Data were collected through observation, interviews, writing tests, and documentation. The result showed that the implementation of the SmartLetter teaching module effectively improved students’ writing skills, with an average score of 84,8 and a classical completion rate of 83.3% (≥75). The integration of PjBL and Deep learning fostered critical thinking skills, empathy, and a reflective understanding of language use. Therefore, the SmartLetter teaching module can be an innovative, and character development in elementary school students